Prescrevendo curvatura escalar de métricas com volume unitário - Santos, Pablo José Cruz dos (2021)
The task of this work is to study with details the results of O. Kobayashi (KOBAYASHI, 1987), which is related with the problem of existence of metrics in closed manifold with unit volume with prescribed scalar curvature. The technique applied by him consists in to use the results obtained by the Yamabe Problem, at leat for manifolds with dimension greater or equal to 3. The sign of the Yamabe invariant is crucial to obtain the results desired. Also, we study the Yamabe invariant of connected sums, and the problem of existence of conformal metrics with scalar curvature arbitrarily large.